الدّور الهامّ للتّدوين والتّلخيص في التّرجمة التّتبعيّة - إبراهيم, ياسر (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يطمح هذا البحث إلى تّاكيد على الدّور الهامّ الذّي تلعبه تقنية التّدوين والتّلخيص في الترجمة التّتبّعيّة. فبقدر ما تكون مهنية المترجم التّتبُّعي في توظيف هذه التقنية، تنعكس جودة فهمه وسبره لمكوِّنات النّص الأصليّ. إذ يغدو المترجم التّتبُّعي قادراً على الاستفادة من التّدوين خلال هذا النّوع من التّواصل الشّفهي بشكلٍ واثقٍ، بامتلاكه للخصائص اللغوية والمتطلّبات البنيوية والاعتبارات الثّقافية والهدف البلاغي للنّصين الأصليّ والهدف. كما ينطوي التّدوين على بعض الإجراءات: كاختيار الإشارات والرّموز الدلالية, والاستماع وعمليات الذّاكرة، واختيار اللغة (الأصلية أو الهدف) والشّيفرة (الكلمة أو الإشارة) في أثناء التّدوين. وتؤثِّر بعض العوامل غير اللغوية في التّدوين مثل: الانتباه والذّاكرة، سرعة التّحدّث، صناعة القرار من بين العديد من العناصر الأخرى. وقد حُدِّدت بعض علائم دور التّدوين في الترجمة المقتضبة والترجمة المستفيضة وفي تدخُّل المترجم. أخيراً، يعتبرُ هذا البحثُ الترجمةَ التّتبعية عمليةً نصّيةً وبالتّالي يحاول تحرّي إبداع المترجم من خلال تطبيقه الماهر لتقنية التّدوين والتلخيص. This piece of research endeavours to emphasize the indispensible role that the technique of note-takig and summarising plays in consecutive interpreting. The more professional the consecutive interpreter in manipulating such a technique, the better his comprehension and persuasion of the ST components will be. Equipped with the linguistic specifications, structural requirements, cultural considerations and the rhetorical purpose of both the ST and the TT, he becomes confidently capable of utilizing note-taking through this type of oral communication. Note-taking, however, subsumes a few procedures: selecting signs and emblematic symbols, listening and memory operations, choosing the language (SL or TL) and the code (word or sign) of note-taking. Some non-linguistic factors influence note-taking: attention and memory, speaking speed, decision making, among many other factors. Some remarks have been made toward identifying the role of note-taking in gist and gloss interpreting, the interpreter's interference. Finally, this paper considers consecutive interpreting a textual process, thus attempts to inspect the creativity of the interpreter through the skilful applicability of the technique of note-taking and summarising.